TYPE OF ARTICLE: ORIGINAL ARTICLE ROLE OF CYTOKERATIN BIOMARKERS IN BREAST CARCINOMA - Yadav, Ritu (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Â  ABSTRACT: Objective:Breast cancer comprises different biological subtypes having varied spectrum of clinical and pathological features with different prognostic and therapeutic implications. This study aimed at the identification of patients on the basis of cancer biomarkers and various clinicopathological parameters. Methods: Fresh paraffin embedded tissue block sample of three hundred fifty patients of breast carcinoma were collected during 2011-2014, from the Pathology department, Pt. B.D Sharma University of Heath Sciences Rohtak, Haryana and studied in detail to determine the correlation between hormone receptor status /cytokeratin (CK) expression along with clinicopathologicalfactors.Theimmunohistochemical assay of three hundred fifty patients of breast cancer was performed.Maximum number of patients (35%) were found in the age group of <40 years. Most of the patients were observed with the grade I (59%), tumor size 2-4.9cm (45%), <4 positive lymph node status for metastasis andinfiltrate ductal carcinoma type (93%).Triple positive and triple negative breast cancer types were studiedto identify the basal and luminal phenotypes on the basis of markers CK5, 14 and CK8/18 expression.Results:The expression of CK5 &14 was found to be significantly associated with tumor grade (P=0.001 and P=0.0001), tumor size (P= 0.001) respectively.Whereas CK8/18 expression did not reveal any significant association with tumor grade,size, lymph node status and histological type of breast carcinoma. Conclusion:In conclusion the prognostic and therapeutic value of research work would be examined and validated further on larger number of samples. Keywords: Breast carcinoma, biomarkers, clinicopathological factors, Cytokeratin, hormone receptor Â 